Iowa RBA, March 4, 1996 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for March 4, 1996. Highlights of the update include sightings of a Great Gray Owl, Northern Shrike, Northern Saw-whet Owl, two first year Glaucous Gulls and three first year Thayer's Gulls. Also included are handwritten notes for the next week's update with sightings of a female White-winged Crossbill and a White-winged Scoter. Epson - sheet feed/flatbed